The Interplay of Learning Motivation and Self-efficacy on English Learning Outcomes of EFL Learners: A Meta-Analysis - Mujiono, Mujiono; Lailul Fitriah; Riza Weganofa (Institut Agama Islam Negeri Palopo, 2024)
Abstract This study aims to describe the relationship between learning motivation (LM) and self-efficacy (SE) in English learning outcomes for EFL learners. LM and SE have significantly related to EFL learners’ learning outcomes. However, there is a need to thoroughly examine learning outcomes in language learning, particularly considering variations in students’ LM. This study aims to conduct a meta-analysis of correlation studies to evaluate the interaction of LM and SE on EFL students' learning outcomes. The evidence for the relationship between LM and SE in EFL students was analyzed using a meta-analysis. The study found that a random model was utilized, and the magnitude of the effect was exceptionally great (d.0576). The meta-analysis computed 11 effects, and the variable analysis moderator examined the study's source, sample size, student major, language learning target, educational level, and instrument type.